Paradoxos e estratégias de adaptação na trajetória universitária discente em relação às metodologias ativas no curso de Medicina da UFSCar - Barbosa, Silvia Helena Pienta Borges (Universidade Federal de São Carlos, 2020)
The present thesis has as object of investigation the trajectory of students of a medical course that presents the curriculum organized through active learning methodologies. Its research problem is the understanding of how the university trajectory is processed and how students develop adaptive strategies in relation to the active learning methodology of the medical course. The objective of this study is to analyse the entrance, the difficulties and the adaptation strategies of the students in their trajectory. The work was carried out from a qualitative and field research. To conduct the research, an online questionnaire was sent to all students of the course in question, with approximately 20% of the questionnaires returned, in addition four group interviews, each interview had two or three students, accounting for nine students interviewed. The questionnaire and interviews were analysed through content analysis and data triangulation, considering Pierre Bourdieu's theory. The results point to a university trajectory that develops differently from the previous school and / or university trajectory of these students, which means that agents have to reconfigure student habitus in this new field, developing adaptation strategies to the course, which include changes in individual study form, attempt to adjust the student habitus prior to the current field, creation of a support network with classmates and veterans and change in the way of viewing the course and teaching-learning. In addition, one of the greatest difficulties encountered by students in the adaptive process is the lack of support from the course in relation to students. This situation leads students, paradoxically, to take the field game seriously given the need to legitimize the field they are part of.
Paradoxes and adaptation strategies in the student university trajectory in relation to active learning in the UFSCar Medicine course
Keywords: Metodologia ativa; Trajetória; Educação médica; Pierre Bourdieu; Campo universitário; Active learning; Trajectory; Medical education; University field; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO